2020
DOI: 10.1177/1056789520957703
|View full text |Cite
|
Sign up to set email alerts
|

Detection and evaluation of barely visible impact damage in woven glass fabric reinforced polyamide 6.6/6 composite using ultrasonic imaging, X-ray tomography and optical profilometry

Abstract: The present experimental work investigates the response of woven glass fabric reinforced polyamide 6.6/6 subjected to drop weight impact loading. The main objective is the development and the introduction of a new experimental procedure/approach, based on different complementary detection techniques, that aims at investigating the damage induced by impact loading in thermoplastic woven fabric composites. The developed approach is intended to be generalized to other types of composite materials. The main idea i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…Different from the damage repairability of self-healing materials (Han et al., 2021; Zhou and Ju, 2019), permanent damages (Miqoi et al., 2020) are retained inside the fiber-reinforced epoxy resin composites after being subjected to impact loads, which directly affects the residual mechanical properties of composite structures. It is necessary to consider the irreversible deformation structure and material damage of LVI as the initial geometry boundary of the CAI model.…”
Section: Resultsmentioning
confidence: 99%
“…Different from the damage repairability of self-healing materials (Han et al., 2021; Zhou and Ju, 2019), permanent damages (Miqoi et al., 2020) are retained inside the fiber-reinforced epoxy resin composites after being subjected to impact loads, which directly affects the residual mechanical properties of composite structures. It is necessary to consider the irreversible deformation structure and material damage of LVI as the initial geometry boundary of the CAI model.…”
Section: Resultsmentioning
confidence: 99%
“…Due to a heterogeneous structure, it occurs at several length scales (laminate, lamina, fibre-matrix, interface etc.). In (Miqoi et al, 2021) it is shown that at low velocity impacts, matrix cracking occurs first.…”
Section: Introductionmentioning
confidence: 99%
“…The engineering industry offers many methods for analyzing the defects in the structures. The NDT analysis of glass fibers using a combination of X-ray tomography, ultrasonic imaging, and optical proliferometry was proposed by Miqoi et al [ 7 ] and on carbon fibers using digital image correlation (DIC) and scanning electron microscopy by Sarasini et al [ 8 ], in addition to experimental compression after impact tests by Talreja et al [ 9 ]. SHM finds its way in detecting such impact damage by performing continuous health monitoring of structures 1.…”
Section: Introductionmentioning
confidence: 99%